2020
DOI: 10.1016/j.artd.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Portable compression devices in total joint arthroplasty: poor outpatient compliance

Abstract: Background: Aspirin and mechanical compression devices are approved means of venous thromboembolism (VTE) prophylaxis after total joint arthroplasty. Prior studies of mechanical compression pumps after joint arthroplasty have been limited to the inpatient setting. The purpose of this study was to evaluate outpatient compliance and utilization factors in a rural population after elective hip or knee arthroplasty. Methods: Utilization for portable pneumatic compression pumps after joint arthroplasty was prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
3
13
1
Order By: Relevance
“…26 Interestingly, Dietz et al observed low rates of VTE (0.8%) in 115 TJA (50 THA and 65 TKA) patients despite poor compliance of portable IPCDs from postoperative day 1 (40 patients, 34.7%) to postoperative day 14 (17 patients, 14.8%) which may question the usefulness of continued mechanical prophylaxis once patients are fully ambulatory. 23 While our results showed no difference in periprosthetic fractures or dislocations between groups, these study findings support our institution's protocol change to discontinue outpatient IPCD use in patients undergoing THA. Prospective RCTs with a large sample size might more definitively address our study 1.5 Â 10 6 (0, -) 0 .…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…26 Interestingly, Dietz et al observed low rates of VTE (0.8%) in 115 TJA (50 THA and 65 TKA) patients despite poor compliance of portable IPCDs from postoperative day 1 (40 patients, 34.7%) to postoperative day 14 (17 patients, 14.8%) which may question the usefulness of continued mechanical prophylaxis once patients are fully ambulatory. 23 While our results showed no difference in periprosthetic fractures or dislocations between groups, these study findings support our institution's protocol change to discontinue outpatient IPCD use in patients undergoing THA. Prospective RCTs with a large sample size might more definitively address our study 1.5 Â 10 6 (0, -) 0 .…”
Section: Discussionsupporting
confidence: 69%
“…20,33 Dietz et al found no bleeding, wound, and infection complications in patients who were compliant with using their mobile IPCDs or not, although their study was not powered to detect a difference. 23 In our study, our results showed no difference in bleeding rates between the two groups (p ¼ 0.79). There was one case of bleeding seen in the control group (0.13%) due to hemorrhage from multiple gastric polyps and two cases (0.19%) in the no-IPCD group (one cases due to gastric ulcer and the other due to rectal bleeding).…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Since the publication of these two guideline reports, there have been 12 original studies evaluating various compression devices used from one day to three months postoperatively. Due to the large range, there appears to be no compelling evidence to suggest an optimal duration of mechanical compression amidst the current era of short-stay hospitalizations 453,458 .…”
Section: - Should Mechanical Compressive Devices Be Used Routinely In...mentioning
confidence: 99%